Download presentation

Presentation is loading. Please wait.

Published byGabriel Hopkins Modified over 5 years ago

1
5.5 The Substitution Rule In this section, we will learn: To substitute a new variable in place of an existing expression in a function, making integration easier. INTEGRALS

2
Due to the Fundamental Theorem of Calculus, it is important to be able to find antiderivatives. However, our antidifferentiation formulas do not tell us how to evaluate integrals such as INTRODUCTION Equation 1

3
To find this integral, we use the problem solving strategy of introducing something extra. The ‘something extra’ is a new variable. We change from the variable x to a new variable u. INTRODUCTION

4
Suppose we let u be the quantity under the root sign in Equation 1, u = 1 + x 2. Then, the differential of u is du = 2x dx. Notice that, if the dx in the notation for an integral were to be interpreted as a differential, then the differential 2x dx would occur in Equation 1. INTRODUCTION

5
So, formally, without justifying our calculation, we could write: Equation 2 INTRODUCTION

6
However, now we can check that we have the correct answer by using the Chain Rule to differentiate the final function of Equation 2: INTRODUCTION

7
In general, this method works whenever we have an integral that we can write in the form INTRODUCTION

8
Observe that, if F’ = f, then because, by the Chain Rule, Equation 3 INTRODUCTION

9
That is, if we make the ‘change of variable’ or ‘substitution’ u = g(x), from Equation 3, we have: INTRODUCTION

10
Writing F’ = f, we get: Thus, we have proved the following rule. INTRODUCTION

11
SUBSTITUTION RULE If u = g(x) is a differentiable function whose range is an interval I and f is continuous on I, then Equation 4

12
SUBSTITUTION RULE Notice that the Substitution Rule was proved using the Chain Rule for differentiation. Notice also that, if u = g(x), then du = g’(x)dx. So, a way to remember the Substitution Rule is to think of dx and du in Equation 4 as differentials.

13
SUBSTITUTION RULE Thus, the Substitution Rule says: It is permissible to operate with dx and du after integral signs as if they were differentials.

14
SUBSTITUTION RULE Find We make the substitution u = x 4 + 2. This is because its differential is du = 4x 3 dx, which, apart from the constant factor 4, occurs in the integral. Example 1

15
SUBSTITUTION RULE Thus, using x 3 dx = du/4 and the Substitution Rule, we have: Notice that, at the final stage, we had to return to the original variable x. Example 1

16
SUBSTITUTION RULE The idea behind the Substitution Rule is to replace a relatively complicated integral by a simpler integral. This is accomplished by changing from the original variable x to a new variable u that is a function of x. Thus, in Example 1, we replaced the integral by the simpler integral

17
SUBSTITUTION RULE The main challenge in using the rule is to think of an appropriate substitution. You should try to choose u to be some function in the integrand whose differential also occurs, except for a constant factor. This was the case in Example 1.

18
SUBSTITUTION RULE If that is not possible, try choosing u to be some complicated part of the integrand, perhaps the inner function in a composite function.

19
Finding the right substitution is a bit of an art. It is not unusual to guess wrong. If your first guess does not work, try another substitution. SUBSTITUTION RULE

20
Evaluate Let u = 2x + 1. Then, du = 2 dx. So, dx = du/2. E. g. 2—Solution 1

21
Thus, the rule gives: SUBSTITUTION RULE E. g. 2—Solution 1

22
Another possible substitution is Then, So, Alternatively, observe that u 2 = 2x + 1. So, 2u du = 2 dx. SUBSTITUTION RULE E. g. 2—Solution 2

23
Thus, SUBSTITUTION RULE E. g. 2—Solution 2

24
SUBSTITUTION RULE Find Let u = 1 – 4x 2. Then, du = -8x dx. So, xdx = -1/8 du and Example 3

25
SUBSTITUTION RULE The answer to the example could be checked by differentiation. Instead, let us check it with a graph.

26
SUBSTITUTION RULE Here, we have used a computer to graph both the integrand and its indefinite integral We take the case C = 0.

27
SUBSTITUTION RULE Notice that g(x): Decreases when f(x) is negative Increases when f(x) is positive Has its minimum value when f(x) = 0

28
So, it seems reasonable, from the graphical evidence, that g is an antiderivative of f. SUBSTITUTION RULE

29
Calculate If we let u = 5x, then du = 5 dx. So, dx = 1/5 du. Therefore, Example 4

30
SUBSTITUTION RULE Find An appropriate substitution becomes more obvious if we factor x 5 as x 4. x. Let u = 1 + x 2. Then, du = 2x dx. So, x dx = du/2. Example 5

31
SUBSTITUTION RULE Also, x 2 = u – 1; so, x 4 = (u – 1) 2 : Example 5

32
SUBSTITUTION RULE Calculate First, we write tangent in terms of sine and cosine: This suggests that we should substitute u = cos x, since then du = – sin x dx, and so sin x dx = – du: Example 6

33
SUBSTITUTION RULE Since –ln|cos x| = ln(|cos x| -1 ) = ln(1/|cos x|) = ln|sec x|, the result can also be written as Equation 5

34
DEFINITE INTEGRALS When evaluating a definite integral by substitution, two methods are possible.

35
One method is to evaluate the indefinite integral first and then use the FTC. For instance, using the result of Example 2, we have: DEFINITE INTEGRALS

36
Another method, which is usually preferable, is to change the limits of integration when the variable is changed. Thus, we have the substitution rule for definite integrals.

37
If g’ is continuous on [a, b] and f is continuous on the range of u = g(x), then SUB. RULE FOR DEF. INTEGRALS Equation 6

38
Let F be an antiderivative of f. Then, by Equation 3, F(g(x)) is an antiderivative of f(g(x))g’(x). So, by Part 2 of the FTC (FTC2), we have: SUB. RULE FOR DEF. INTEGRALS Proof

39
However, applying the FTC2 a second time, we also have: SUB. RULE FOR DEF. INTEGRALS Proof

40
Evaluate using Equation 6. Using the substitution from Solution 1 of Example 2, we have: u = 2x + 1 and dx = du/2 Example 7 SUB. RULE FOR DEF. INTEGRALS

41
To find the new limits of integration, we note that: When x = 0, u = 2(0) + 1 = 1 and when x = 4, u = 2(4) + 1 = 9 Example 7 SUB. RULE FOR DEF. INTEGRALS

42
Thus, Example 7 SUB. RULE FOR DEF. INTEGRALS

43
Observe that, when using Equation 6, we do not return to the variable x after integrating. We simply evaluate the expression in u between the appropriate values of u. SUB. RULE FOR DEF. INTEGRALS Example 7

44
Evaluate Let u = 3 - 5x. Then, du = – 5 dx, so dx = – du/5. When x = 1, u = – 2, and when x = 2, u = – 7. Example 8 SUB. RULE FOR DEF. INTEGRALS

45
Thus, Example 8 SUB. RULE FOR DEF. INTEGRALS

46
Calculate We let u = ln x because its differential du = dx/x occurs in the integral. When x = 1, u = ln 1, and when x = e, u = ln e = 1. Thus, Example 9 SUB. RULE FOR DEF. INTEGRALS

47
As the function f(x) = (ln x)/x in the example is positive for x > 1, the integral represents the area of the shaded region in this figure. SUB. RULE FOR DEF. INTEGRALS Example 9

48
SYMMETRY The next theorem uses the Substitution Rule for Definite Integrals to simplify the calculation of integrals of functions that possess symmetry properties.

49
INTEGS. OF SYMM. FUNCTIONS Suppose f is continuous on [–a, a]. a. If f is even, [f(–x) = f(x)], then b. If f is odd, [f(-x) = -f(x)], then Theorem 7

50
We split the integral in two: Proof - Equation 8 INTEGS. OF SYMM. FUNCTIONS

51
In the first integral in the second part, we make the substitution u = –x. Then, du = – dx, and when x = – a, u = a. INTEGS. OF SYMM. FUNCTIONS Proof

52
Therefore, Proof INTEGS. OF SYMM. FUNCTIONS

53
So, Equation 8 becomes: Proof - Equation 9 INTEGS. OF SYMM. FUNCTIONS

54
If f is even, then f(–u) = f(u). So, Equation 9 gives: INTEGS. OF SYMM. FUNCTIONS Proof a

55
If f is odd, then f(–u) = –f(u). So, Equation 9 gives: INTEGS. OF SYMM. FUNCTIONS Proof b

56
Theorem 7 is illustrated here. INTEGS. OF SYMM. FUNCTIONS

57
For the case where f is positive and even, part (a) says that the area under y = f(x) from -a to a is twice the area from 0 to a because of symmetry. INTEGS. OF SYMM. FUNCTIONS

58
Recall that an integral can be expressed as the area above the x-axis and below y = f(x) minus the area below the axis and above the curve. INTEGS. OF SYMM. FUNCTIONS

59
Therefore, part (b) says the integral is 0 because the areas cancel. INTEGS. OF SYMM. FUNCTIONS

60
As f(x) = x 6 + 1 satisfies f(–x) = f(x), it is even. So, Example 10 INTEGS. OF SYMM. FUNCTIONS

61
As f(x) = (tan x)/ (1 + x 2 + x 4 ) satisfies f(–x) = –f(x), thus f(x) is odd and, Example 11 INTEGS. OF SYMM. FUNCTIONS

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google